End users' purchasing task involvement, power and influence strategies in organizational buying. Issue 1 (27th November 2018) - Pedeliento, Giuseppe; Andreini, Daniela; Bergamaschi, Mara; Salo, Jari
Abstract : Purpose: End users are often involved in organizational buying, but very little is known about the role that they play and how they influence purchasing decisions. This study aims to explore the factors behind end users' attempts to influence purchasing and the strategies they use. Design/methodology/approach: The research draws on the concept of purchasing task involvement, which describes the feelings of personal relevance that a buying center member has for a specific organizational purchasing decision. This concept is used to gain a deeper understanding of users' influence in organizational purchasing and link it to sources of power and the corresponding influence strategies. The study is based on 90 in-depth interviews with buyers, drivers and sellers of heavy trucks. Findings: End users' purchasing task involvement is only marginally determined by the product's performance or technical features. Purchasing task involvement leads to influence when there are specific power relationships between the buyer and the user and under specific circumstances. Originality/value: This is the first study that links end users' purchasing task involvement, power and influence strategies in organizational buying.